ANALISIS EFISIENSI USAHATANI DAN PEMASARAN MELON DI KECAMATAN MUNCAR KABUPATEN BANYUWANGI - A. Zubaidi; A. A. Sa`diyah (Universitas Tribhuwana Tunggadewi, 2012)
The study aims to determine the cost of production, revenue, profits and melon farming efficiency, also cost, margin and efficiency of each marketing agencies in Muncar Sub District, Banyuwangi Regency. The study was conducted using descriptive methods with primary data consisted of 42 farmers and 11 traders in Muncar Sub District. The sample i.e. traders was taken using snow ball sampling method. The results obtained that the average production cost of melon farm was IDR 35,997,500/ha, farmers' income was IDR 24,802,500/ha, and farming efficiency was R/C = 1.68 this means that the farm was feasible and can proceed. The share value received by farmers in the marketing channels I was 57.58% with margin of IDR 1,400.-; and the marketing channels II was 69.69% with margin of IDR 1,000. The marketing efficiency of both existing marketing institutions was k/b>1 which means that both the existing marketing channel was quite efficient